2021
DOI: 10.1186/s12284-020-00451-y
|View full text |Cite
|
Sign up to set email alerts
|

OsMS188 Is a Key Regulator of Tapetum Development and Sporopollenin Synthesis in Rice

Abstract: Background During anther development, the tapetum provides essential nutrients and materials for pollen development. In rice, multiple transcription factors and enzymes essential for tapetum development and pollen wall formation have been cloned from male-sterile lines. Results In this study, we obtained several lines in which the MYB transcription factor OsMS188 was knocked out through the CRISPR-Cas9 approach. The osms188 lines exhibited a male-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 46 publications
(92 reference statements)
0
73
0
Order By: Relevance
“…Because the slr1‐5 and osms188 mutants share similar anther developmental phenotypes, we compared the gene expression profiles of these two mutants (Han et al ., 2021) (Fig. S3; Table S10).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because the slr1‐5 and osms188 mutants share similar anther developmental phenotypes, we compared the gene expression profiles of these two mutants (Han et al ., 2021) (Fig. S3; Table S10).…”
Section: Resultsmentioning
confidence: 99%
“…DELLA proteins, which do not contain a DNA‐binding domain, generally activate or suppress target gene expression by interacting with other TFs. We noted that the anther development phenotypes and gene expression pattern of osms188 share similarity to those of slr1‐5 (Figs 1, 2, 4) (S. Zhang et al ., 2010; Pan et al ., 2020; Han et al ., 2021; Xiang et al ., 2021). Additionally, the gene expression profile regulated by SLR1 was similar to that regulated by OsMS188 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These DEGs included two bHLH TFs ( BHLH089 and BHLH010 ), two extensin peroxidases ( PRX9 and PRX40 ), tapetum-specific TAP35/TAP44 , and two CALS5 genes. During pollen formation, tapetum cells play central roles in callose degradation, pollen exine formation, and the provision of various nutrients for pollen development ( Han et al, 2021 ). Our cytological characterization of the abortive anthers showed that the tapetum cells (which surround the microspores and provide crucial enzymes and nutrients for microsporogenesis and pollen wall development, Ferguson et al, 2017 ) were degraded.…”
Section: Discussionmentioning
confidence: 99%